La persona como vocación en Romano Guardini. Fundamentación desde la Antropología trascendental de Leonardo Polo - Tinizaray, Ana Bastidas (Alpha omega, 2019)
According to R. Guardini, vocation is the free communion of the person with his Creator, in the light of which the person truly comes to know himself. Leonardo Polo considers that vocation is the person himself, whose existence is the gift of an act of being, coexistent and destined to give itself freely, and which awaits being accepted. Vocation is something personal, something radically new; nevertheless, its manifestation or its state of life is in accordance with the community within which it is formed. The family represents the basic form of community, on the basis of which the other communities, which form every vocation, can be understood.